Composite control for switched impulsive time-delay systems subject to actuator saturation and multiple disturbances. (February 2020) - Wei, Yunliang; Liu, Guo-Ping
Abstract: This paper focuses on the composite control problem for a class of uncertain switched impulsive systems with time-varying time delay, actuator saturation and multiple disturbances which are matched and mismatched with continuous control inputs. The system under consideration involves parameter uncertainties and nonlinear uncertainties, and the actuators of both continuous control inputs and impulsive control inputs are considered to be limited by saturation. Actuator saturation brings great difficulties and challenges to implement composite control based on disturbance compensation, especially when the system is with matched disturbances. A novel switching composite controller and a switching state feedback controller are constructed respectively such that the performance requirement of anti-disturbance control for the system is achieved, the former of which can realize rejection of the matched disturbances simultaneously. Based on the treatment of the saturation as polytopic differential inclusion, the design conditions of the controllers are developed to guarantee the locally robustly asymptotic stability and robust H ∞ disturbance attenuation of the closed-loop system with an estimation of the domain of attraction. Finally, a simulation example is performed to validate the feasibility of our results.